Analisis Risiko Kecelakaan Kerja Menggunakan Metode JSA Pada Departemen Pengelasan UPTD Balai Latihan Kerja Industri Balikpapan - Fitrah Fajrian (Journal of Industrial Innovation and Safety Engineering (JINSENG), 2024)
UPTD Industrial Work Training Center is an agency engaged in professional training to gain skills or deepen expertise in their respective fields. In these fields, especially in the training department, there are often potential hazards. The results of work accidents in the training process at the Balikpapan Industrial Work Training Center UPTD using the Job Safety Analysis (JSA) method. This method starts from identifying potential hazards, then collecting data directly which aims to obtain information about the hazards that can occur at each step of the activity and solutions as controls. In the welding process there are several stages, namely in the first stage doing bench work practices, manual materials, welding, material cutting then electric welding. The JSA Training found 66 potentially hazardous events including: Bench Work Process as many as 15 potential hazards, manual cutting machines as many as 4 potential hazards, gas welding as many as 18 potential hazards, machine cutting as many as 13 potential hazards, electric welding 10 potential hazards and quality process control as many as 6 potential hazards. In the implementation of the welding training, the most dangerous potential is gas welding with 18 potential hazards, while the quality control stage has the least potential hazard compared to other stages. Hazard management at the UPTD of the Balikpapan Industrial Work Training Center is carried out by Engineering Control, Administration, and using PPE as ways to prevent work accidents.